Kemampuan Memecahkan Masalah dan Hasil Belajar Kognitif Melalui PBL pada Materi Sistem Respirasi: Ability to Solve Problems and Cognitive Learning Outcomes Through PBL on the Topic of Respiratory System - Desi Sri Lestari; Muhammad Syaipul Hayat; Rivanna Citraning Rachmawati; Moch. Ansori (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The ability to solve problem of students in the 21st century is very important. This study aims to determine the ability to solve problems and cognitive learning outcomes of students with the PBL (Problem Based Learning) learning model. The method used is a qualitative approach to descriptive research. Techniques for collecting data on the results of LKPD answers and learning outcomes tests. The sample of this research was 36 students in class XI MIPA 8 at SMA Negeri 2 Semarang. The results of the research on students' problem solving abilities obtained a percentage of 77% in the good category. Meanwhile, cognitive learning outcomes for students are higher, with an average of 90 compared to KKM (Minimum Completeness Criteria), which is 80. Key words: Solving problems, PBL, Cognitive learning outcomes Â AbstrakKemampuan memecahkan masalah pada peserta didik di abad 21 ini sangat penting. Penelitian ini bertujuan untuk mengetahui kemampuan memecahkan masalah dan hasil belajar kognitif peserta didik dengan model pembelajaran PBL (Problem Based Learning). Metode yang digunakan yaitu pendekatan kualitatif jenis penelitian deskriptif. Teknik pengumpulan data hasil jawaban LKPD dan tes hasil belajar. Sampel penelitian ini adalah peserta didik kelas XI MIPA 8 di SMA Negeri 2 Semarang berjumlah 36 orang. Hasil penelitian kemampuan memecahkan masalah pada peserta didik didapatkan persentase 77% dengan kategori baik. Sedangkan, hasil belajar kognitif pada peserta didik lebih tinggi yaitu dengan rerata 90 dibandingkan dengan KKM (Kriteria Ketuntasan Minimal) yaitu 80. Kata kunci: Memecahkan masalah, PBL, Hasil belajar kognitif.